PREVENTIVE BEHAVIORS FOR DENGUE HEMORRHAGIC FEVER - Masrur; Ali Harokan; Arie Wahyudi (LPPM STIKES Al-Ma'arif Baturaja, 2024)
Dengue fever is a viral infection caused by the dengue virus which is transmitted to humans through the bite of an infected mosquito. About half of the world's population is now at risk of dengue fever with an estimated 100–400 million infections occurring annually. This study aims to determine factors related to dengue prevention behavior in the East Ogan Komering Ulu District Health Service in 2024. The design of this research is quantitative with a cross-sectional approach. The population of this study was visits to the Gumawang Health Center in 2024. The sample in this study consisted of 93 respondents. The sampling method used purposive sampling. This research was carried out on 15-26 February 2024. Data was collected using a questionnaire. Bivariate data analysis used the Chi-Square test and multivariate logistic regression. Data collection using questionnaires. Results of statistical test analysis using the Chi-Square statistical test. The results of the study knowledge (p value 0.022), draining the landfill (p value 0.047), preventive measures (p value 0.005) and ventilation (p value (0.017). Age (p value 0.35), mosquito wire installation (p value 0.47) with dengue hemorrhagic fever (DHF) prevention behaviour at the East Ogan Komering Ulu District Health Office in 2024. The most dominant factor with dengue hemorrhagic fever (DHF) prevention behaviour is DHF prevention measures (p Value = 0.003) (OR 0.252). Conclusion There is a relationship between knowledge, landfill draining, preventive measures and ventilation. For the Health Office to carry out dengue prevention activities, carried out routinely and scheduled integrated in basic health services.